Residual dizziness after BPPV management: exploring pathophysiology and treatment beyond canalith repositioning maneuvers - Özgirgin, O. Nuri; Kingma, Herman; Manzari, Leonardo; Lacour, Michel (Frontiers in Neurology, 2024)
Benign paroxysmal positional vertigo (BPPV), a condition seen often in clinical practice, is generally well managed with canalith repositioning maneuvers (CRMs). However, a significant number of patients report residual dizziness (RD) symptoms for weeks or months after a successful CRM. Although CRMs remain the fundamental approach to treating BPPV, the pathophysiology of BPPV is complex, and we explore the association between BPPV and RD and identify potential management options, based on both known and proposed causes of BPPV and/or RD, such as small otoconial particles left in the canals or insufficient vestibular compensation. We selected Frontiers in Neurology due to its wide and broad readership, with the hope of encouraging physicians to understand the importance of RD and how it might be managed, based on the patient's history and likely etiology. Although almost exclusively benign, RD is very unpleasant and detrimental to quality of life. The very success of CRMs may have resulted in other contributory pathologies being overlooked. This article seeks to highlight these pathologies and how they may be addressed in clinical practice by taking a holistic approach to the management of BPPV and RD.